An ecosystem approach to integrated coastal zone management: Case study on the Gresik Regency, East Java - Mauludiyah; Nur Maulida Safitri (Journal of Marine Resources and Coastal Management, 2022)
Gresik Regency is one of the industrial development areas in East Java Province due to its strategic location. This region has the opportunity to actively integrate the ecosystem into development planning. Management of integrated coastal areas is widely advocated at all levels of government as a means of delivering sustainable development in coastal areas. This study was conducted to determine the level of impact caused by each activity cumulatively on coastal and marine ecosystems in Gresik Regency. In general, this study is oriented towards collecting data of marine pollution level from various substances and sources, as well as changes over time in the status of the marine environment in Gresik Regency. The results showed that the increase in population growth accompanied by an increase in the amount of waste, as well as an increase in industry, port and agricultural activities in coastal areas of Gresik Regency require special attention in the management of the coastal and marine environment in Gresik Regency. The use of coastal and marine areas of Gresik Regency can lead to loss of biodiversity, as well as decreased stability and resilience of ecosystems in coastal and marine areas. It is necessary to take into account the pressures and impacts due to activities in coastal and marine areas and then propose the most appropriate development solutions within the framework of Integrated Coastal Zone Management in Gresik Regency.